Implementation of Zakat Law in Indonesia: Between Religious Obligation and State Regulation - Muhammad Halim; Yogi Finanda; Asrizal Asrizal (Qanun: Jurnal Hukum Keluarga Islam, 2025)
Zakat is one of the obligatory acts in Islamic teachings that plays a significant role in economic equity and social welfare. In Indonesia, the implementation of zakat law faces challenges in balancing religious obligations and state regulations. Although it is regulated under Law Number 23 of 2011 concerning Zakat Management, its implementation remains suboptimal due to factors such as public awareness, integration with the taxation system, and the effectiveness of zakat management institutions. This study employs a qualitative method with a literature review approach to analyze the implementation of zakat law in Indonesia from the perspective of Islamic law and state regulations. The findings reveal that while zakat has a strong legal basis in Islam, in the national legal system it remains voluntary and has not yet become a legally binding obligation like taxes. The management of zakat by the National Amil Zakat Agency (BAZNAS) and Zakat Management Institutions (LAZ) is not yet fully integrated with the country’s fiscal policies, resulting in the underutilization of zakat as an economic instrument. Furthermore, the lack of transparency and accountability in some zakat institutions reduces public trust in distributing zakat through official channels. This study concludes that stronger policies are needed to optimize the role of zakat, including broader public awareness, integration with tax policies, and improved accountability of zakat institutions.